2014
DOI: 10.1517/14740338.2014.971009
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of non-vitamin K oral anticoagulants in non-valvular atrial fibrillation: a Bayesian meta-analysis approach

Abstract: Warfarin ranked worst for all-cause mortality and intracranial bleedings and had a nil probability of ranking first for any outcome. The risk of major bleeding versus warfarin was lower with apixaban, dabigatran 110 mg, and both doses of edoxaban. All agents reduced the risk of intracranial bleeding versus warfarin. Edoxaban 30 mg was the best among the treatments being compared for major and gastrointestinal bleeding. Dabigatran 150 mg was the best for stroke and systemic embolism. This study suggests that NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…Sharma et al [ 26 ] performed a SR analysing patients aged 75 years or older and presented subgroup results for patients with AF. Six SRs performed a network meta-analysis (NMA) [ 40 , 42 , 43 , 46 , 67 , 68 ] and four showed subgroup results for each NOAC [ 26 , 32 , 43 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sharma et al [ 26 ] performed a SR analysing patients aged 75 years or older and presented subgroup results for patients with AF. Six SRs performed a network meta-analysis (NMA) [ 40 , 42 , 43 , 46 , 67 , 68 ] and four showed subgroup results for each NOAC [ 26 , 32 , 43 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent network meta-analysis published in 2018 compared different NOACs for their risk of ICH in patients with AF or venous thromboembolism (VTE), which drew a conclusion that dabigatran110 (SUCRA 0.83) ranked as the safest drug, but the NMA did not include the low dose edoxaban [27]. Another Bayesian meta-analysis published in 2015 also concluded that edoxaban30 was the safest drug with regard to preventing major bleeding, followed by dabigatran110 in patients with AF [28], which was closely consistent with our findings in patents with normal or mild renal function.…”
Section: Discussionmentioning
confidence: 99%
“…A prior Bayesian meta‐analysis by Verdecchia et al . published in 2015 used data from major trials in which DOACs were compared with warfarin for stroke prevention in NVAF (RE‐LY, ROCKET‐AF, ARISTOTLE and ENGAGE AF). They also ranked the anticoagulants and, as in our analysis, found that dabigatran 110 mg was the safest DOAC and rivaroxaban the least safe DOAC with regards to ICH.…”
Section: Discussionmentioning
confidence: 99%